2019
DOI: 10.1136/sextrans-2019-054208
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C infection among men who have sex with men living with HIV in New York City, 2000–2015

Abstract: ObjectivesTo calculate the rate of hepatitis C virus (HCV) among HIV-infected men who have sex with men (MSM) with no reported history of injection drug use (IDU), and to assess whether disparities exist in HIV/HCV coinfection by race/ethnicity and neighbourhood poverty level within this population in New York City.MethodsHIV-positive men who reported sex with men and did not report IDU at the time of HIV diagnosis, diagnosed through 2015 and alive as of 2000, were matched to people with HCV first reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Fifty‐six studies fulfilled the inclusion criteria, as shown in Table 1 , comprising a total of 309203 MSM PLHIV. Switzerland contributed five studies, 18 , 20 , 37 , 38 , 39 United States had 11 studies, 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Spain had four studies, 51 , 52 , 53 , 54 Netherlands had four studies, 55 , 56 , 57 , 58 three studies were from France, 17 , 59 , 60 six studies were from Taiwan, 22 , 61 , 62 , 63 , 64 , 65 eight studies were from United Kingdom, 19 , 21 , 23 , 25 , 66 , 67 , 68 , 69 two studies were from Europe, 70 , 71 two studies from Japan, 24 , 72 two studies from Australia. 73 , 74 One study each were from Belgium, 75 …”
Section: Resultsmentioning
confidence: 99%
“…Fifty‐six studies fulfilled the inclusion criteria, as shown in Table 1 , comprising a total of 309203 MSM PLHIV. Switzerland contributed five studies, 18 , 20 , 37 , 38 , 39 United States had 11 studies, 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 Spain had four studies, 51 , 52 , 53 , 54 Netherlands had four studies, 55 , 56 , 57 , 58 three studies were from France, 17 , 59 , 60 six studies were from Taiwan, 22 , 61 , 62 , 63 , 64 , 65 eight studies were from United Kingdom, 19 , 21 , 23 , 25 , 66 , 67 , 68 , 69 two studies were from Europe, 70 , 71 two studies from Japan, 24 , 72 two studies from Australia. 73 , 74 One study each were from Belgium, 75 …”
Section: Resultsmentioning
confidence: 99%
“… 11 Because of the possible high degree of connectivity in these networks, the potential for sustained transmission, including HCV reinfection after treatment, has been flagged as a factor that may undermine HCV microelimination efforts. 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%
“…For example, populations with low levels of phylogenetic clustering could indicate that loosely connected sexual or drug use networks exist. Previous studies have found that HCV acquisition is associated with younger age, 24 female sex (vs. male sex), 25 recent injection drug use, 26 homelessness, 27 material deprivation, 14 and sexual behavior such as serosorting 28 or chemsex. 29 Investigation into the extent of HCV phylogenetic clustering and patterns and correlates of clustering with these previously identified factors is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations